2003
DOI: 10.1017/s0950268803008690
|View full text |Cite
|
Sign up to set email alerts
|

Use of hospitalization and pharmaceutical prescribing data to compare the prevaccination burden of varicella and herpes zoster in Australia

Abstract: The aims of the study were to compare the burden of varicella and herpes zoster in Australia. No national surveillance exists for varicella or herpes zoster. We used hospital morbidity data from 1993-9 and pharmaceutical prescribing data from 1995-9. In the financial year 1998/99, there were 4718 hospitalizations for zoster compared to 1991 for varicella. For varicella the mean age of patients was 15 years compared to 69 years for zoster. The mean length of stay in hospital was 4.2 days for varicella and 12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 24 publications
4
55
0
Order By: Relevance
“…These findings are consistent with other Australian analyses of national hospitalisation data. 18 Our estimate of the overall rate of varicella-related hospitalisations, 2.7 per 10,000 hospitalisations, was also consistent with international literature in pre-vaccination era populations e although these studies have tended to focus on paediatric populations. 19,20 Diagnoses of varicella infection made up a greater proportion of locum consultations relative to the VAED data.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with other Australian analyses of national hospitalisation data. 18 Our estimate of the overall rate of varicella-related hospitalisations, 2.7 per 10,000 hospitalisations, was also consistent with international literature in pre-vaccination era populations e although these studies have tended to focus on paediatric populations. 19,20 Diagnoses of varicella infection made up a greater proportion of locum consultations relative to the VAED data.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the disease burden due to HZ is higher than that due to varicella, with average annual hospitalization rates of 24/100,000 population, or 10/100,000 population for HZ as the principal diagnosis [5]. The mortality due to HZ is 2-3 times higher than that due to varicella [3,5]. It has been estimated that 1157,000 cases of HZ occurred in the Australian community in 1999, at a rate of 830/100,000 population [3].…”
mentioning
confidence: 99%
“…The mortality due to HZ is 2-3 times higher than that due to varicella [3,5]. It has been estimated that 1157,000 cases of HZ occurred in the Australian community in 1999, at a rate of 830/100,000 population [3]. New Zealand.…”
mentioning
confidence: 99%
“…Two studies have shown similar or only marginally higher hospitalisation rates for zoster [45,64]. It can be speculated that coincidental zoster may occur, especially among elderly hospitalised adults with long hospital stays, some of who will die from other causes [45].…”
Section: Data From Mathematical Modelsmentioning
confidence: 99%